Evaluasi Pemeriksaan Tes Buta Warna Menggunakan Metode Ishihara Berbasis Google Form Menggunakan Buku Ishihara - Syahril Saini; Elvie Febriani Dungga; Ita Sulistiani (Indonesian Journal of Pharmaceutical Education, 2022)
This article background about the availability of ishihara book is very rare in rural areas because of its quite expensive price. Therefore, in this current research, the researcher uses the Google Form-based  ishihara book method which is relatively new which can make it easier to do a color blindness test. The research design employs an analytical survey method with a cross sectionl multisite study approach. The samples are 178 active students in 8th semester in faculties on campus 1 UNG where they are determined by accidental sampling. The research findings show that the color blindness test using ishihara book and google form is carried out on 178 (100%) active students in 8th semester of the total samples, 174 (97,7%) do not experience color blindness whereas 4 student (2,3%) have partial green color blindness. In conclusion, the results of evaluation of the sensitivity and specificity of google form towards the golden standard of ishihara book are 100% sensitivity and 100% specificity.